An Optimum Combination of Absorptive and Diffusing Treatments for Classroom Acoustic Design. Issue 2 (June 2014) - Choi, Young-Ji
The present study investigates an optimum combination of absorptive and diffusing treatments for achieving preferred acoustics in classrooms. The measurements were carried out in a 1/10 scale model classroom, adding different amounts of absorptive and diffusing materials to one or more of five surfaces of the room. Adding diffusers on 25% of the ceiling area with the other 75% absorptive was more beneficial for achieving higher G50 and G values than adding absorptive materials on the entire ceiling. Adding absorptive materials on the entire ceiling area and diffusers on the front or side wall was beneficial for achieving shorter T30, EDT values and higher C50 values. Adding diffusers on the front or side wall slightly increased G50 and G values by more than 1 JND. Adding diffusers on the ceiling and lower front wall or side wall and adding diffusers on the ceiling a absorptive materials on the lower front wall were selected for consideration as the more successful treatments for classroom acoustic design.